THE BEST MICROTEACHING PRACTICE PLATFORM: OFFLINE, ZOOM, OR WHATSAPP GROUP? - Rismiyanto Rismiyanto; Fitri Budi Suryani (Universitas Muria Kudus, 2021)
Teaching practice may be done in various platforms in this modern era. The platforms enable the interaction of students and student teachers in Microteaching practice to be implemented in offline face to face class as well as in online classes. They are optionally implemented; even the current worldwide pandemic situation forces the online platforms to be implemented in higher frequency. This research is aimed at finding the best Microteaching practice platform by comparing the student teachers’ Microteaching practice achievement as well as their perception in Microteaching Class by using offline, synchronous, and asynchronous platforms of learning during this pandemic at English Education Department Muria Kudus University. Through an expose-facto design this research shows that the best Microteaching practice platform uses Zoom Meeting. This refers to the comparison of the student teachers’ best Microteaching practice achievement scores and opinion of using offline, Zoom, and WhatsApp Group platforms; and the result of the student teachers’ opinion indicates that they basically prefer having offline teaching platform; and supporting that Zoom Meeting is as the best Microteaching practice platform, they have reasons: they felt more comfortable and confident; they felt more efficient; they felt not being directly observed; and they had bigger freedom in practicing teaching.